2011
DOI: 10.1152/ajpcell.00117.2011
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent inhibition of adrenal TREK-1 channels by angiotensin II and ionomycin

Abstract: Bovine adrenocortical cells express bTREK-1 K ϩ (bovine KCNK2) channels that are inhibited by ANG II through a Gq-coupled receptor by separate Ca 2ϩ and ATP hydrolysis-dependent signaling pathways. Whole cell and single patch clamp recording from adrenal zona fasciculata (AZF) cells were used to characterize Ca 2ϩ -dependent inhibition of bTREK-1. In whole cell recordings with pipette solutions containing 0.5 mM EGTA and no ATP, the Ca 2ϩ ionophore ionomycin (1 M) produced a transient inhibition of bTREK-1 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…; Enyeart et al . ). The findings presented here are in good agreement with the activation of TREK current by PIP 2 and other phospholipids like PIP (Chemin et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Enyeart et al . ). The findings presented here are in good agreement with the activation of TREK current by PIP 2 and other phospholipids like PIP (Chemin et al .…”
Section: Discussionmentioning
confidence: 97%
“…For TREK-1 it has been shown that a decrease in membrane PIP 2 levels promotes channel closing via protein kinase A and that the membrane potential regulation of the channel is sensitive to PIP 2 (Chemin et al 2005(Chemin et al , 2007Lopes et al 2005Lopes et al , 2007Segal-Hayoun et al 2010). Alternatively TREK-1 inhibition by other components of the G αq /PLCβ pathway, namely PKC, Ca 2+ and DAG, has been suggested (Chemin et al 2003;Murbartian et al 2005;Enyeart et al 2011). The findings presented here are in good agreement with the activation of TREK current by PIP 2 and other phospholipids like PIP (Chemin et al 2005;Segal-Hayoun et al 2010).…”
Section: Pip 2 -And Dag-dependent Regulation Of Ion Channels In Tc Nementioning
confidence: 99%
“…The activity of the TREK-1 channel has been shown to be regulated by numerous factors, including AA, pH, stretch, phosphorylation, nitric oxide, temperature, and others (20,(22)(23)(24)57). Here we provide provocative evidence that pregnancy regulates the channel, such that cells from nonpregnant women do not activate when stimulated by AA, despite expression of the channel (13), albeit at a lower level than during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in bovine AZF cells, AngII inhibits TREK-1 currents by separate Ca 2+ - and ATP hydrolysis–dependent pathways (J.J. Enyeart et al, 2005, 2011; Liu et al, 2007). It will be interesting to determine whether AngII inhibits the noninactivating K + current in human cells by dual signaling pathways.…”
Section: Discussionmentioning
confidence: 99%